(untitled) (Global Journal of Human-Social Science, 2012)
This paper dealt with principals attitude towards corporal punishment in Delta State secondary schools It discussed an overview of corporal punishment in schools justification and criticism of school corporal punishment guidelines in imposing corporal punishment in schools effects of corporal punishment on students and reason why school corporal punishment should be banned It is therefore recommended that government should introduce and pass legislations prohibiting the use of corporal punishment in public schools and that teachers and school administrators should be provided with tools and resources necessary to develop safe and effective methods for encouraging positive student s behavior It also recommended that that the use of corporal punishment be discouraged in the school system and there is need for principals to employ better disciplinary techniques that would yield better results